Mindfulness Based-Asset in Accounting: Interdisciplinary Perspective - Driana leniwati; Endang Dwi Wahyuni (Universitas Muhammadiyah Surakarta, 2022)
This study aims to construct the concept of assets using a revised-hedonic treadmill theory approach. By using postmodernism paradigm with constructionism approach in case study design, this research tries to integrate concept of asset in accounting with hedonic treadmill theory to construct a new concept of asset. Empirical data obtained through in-depth interviews with 21 bank employees with various grade positions and working period which were grouped into Assistant (ASST), Assistant Manager (AMGR), Manager (MGR), Assistant Vice President (AVP), and Vice President (VP) in Indonesia. The data were analyzed using the framework of a revised-hedonic treadmill premises as an analytical tool.The result of this research is a mindfulness concept of asset which includes asset as want, asset as need, and asset as blessing. The variation meaning of assets are formed due to events, experiences, or incident both physically and spiritually which ultimately make humans adapt to form self-awareness. They contemplate and finally make their own choices of happiness. At that point, humans are truly at a turning point without going through the assessment of mind. Only a sense of divinity on their heart. Because basically having assets is a mandate entrusted by God to humans so that assets are not the ultimate goal of the pursuit of happiness, but having sufficient and blessings asset will bring people to a sense of peace and gratitude. In essence, humans will seek happiness towards the meaning of life. The mindfulness concept of asset is expected to change the mindset of most people that assets are accumulated not for want but need and blessing. Having sufficient assets are a way to achieve God's blessing and bring humans to the meaning of life that leads to true happiness.